HIGH CRITICAL-CURRENT DENSITIES IN (TL0.5PB0.5)SR2CA2CU3O9 WITH TC UP TO 115-K - Liu, R; Zheng, D; Loram, J; Mirza, K; Campbell, A; Edwards, P (1992)
A high critical-current density was observed in the material (Tl 0.5Pb0.5)Sr2Ca2Cu3O 9. Based on magnetic-hysteresis measurements, this single (insulating) Tl-O layer material has a Jc value of 1.24×10 5 A/cm2 when measured at a temperature of 77 K and a field of 1 T. This value of Jc is comparable to that measured here for YBa2Cu3O7 (1.04×105 A/cm 2), having single-conducting Cu-O chains, but considerably greater than the value for the material Tl2Ba2Ca 2Cu3O10 with double (insulating) Tl-O layers in which no hysteresis was observed under these same conditions. Our results from specific heat measurements indicate that the (Tl0.5Pb 0.5)Sr2Ca2Cu3O9 compound has a three-dimensional character due to the enhancement of the superconducting coupling along the c axis between the Cu-O planes and thus results in an increase in Jc compared to the two-dimensional Bi- and Tl-2212 and 2223 [e.g., (Bi or Tl)2(Sr or Ba)2CaCu2O 8 and (Bi or Tl)2(Sr or Ba)2Ca 2Cu3O10, respectively] compounds. We believe that the high Jc is associated with an increase in the irreversibility field, rather than an increase in pinning centers.